Factors that interfere with adherence to pharmacological treatment in hypertensive elderly - Cardoso, Galvaladar da Silva (2021)
Introduction: Systemic arterial hypertension is directly linked to the functional and / or structural changes of the target organs, thus increasing the risk for the development of cardiovascular diseases. In this context, the quality of life of elderly hypertensive patients is directly affected by the population's lack of knowledge and awareness about the disease and the importance of adherence to drug treatment. Objective: To identify in the literature the factors that influence elderly people with arterial hypertension to not adhere to drug treatment. Methodology: This is an integrative literature review carried out from February to April 2020 in the following databases: Nursing Database, Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online and Scientific Electronic Library Online. Used the elderly descriptors, hypertension and medication adherence. Results: The literature has shown that several factors can contribute to adherence or not to the treatment of arterial hypertension, with emphasis on those related to the disease, treatment, the patient, psychosocial aspects, beliefs, lifestyle, institution and the relationship with the health team. Conclusion: The research findings reinforce the importance of implementing strategies that aim to contribute to the development of attitudes that collaborate with good practices of adherence to the pharmacological treatment of hypertensive elderly people.